Repentance in Nicholas Sparks’ Novel The Last Song: A Literary Psychological Analysis - Pardi Pardi; Lavia Amalia Arun (Universitas Islam Sumatera Utara, 2026)
This study examines the processes of repentance in Nicholas Sparks' The Last Song, focusing on the protagonist's experiences of resentment and reconciliation. The protagonist's emotional estrangement stems from misunderstandings toward his father and friend, as well as a lack of honesty and effective communication. The objective of this research is to identify and analyze the specific forms and sequential stages of repentance exhibited by the protagonist as a response to these relational conflicts. To achieve this, the study adopts a descriptive qualitative approach, following the framework proposed by Creswell (2013), allowing the analysis and results to be presented in a detailed and interpretive manner. The findings reveal two primary forms of repentance: repentance toward his father and repentance toward his friend, each comprising stages of acknowledgment of wrongdoing, emotional reflection, and efforts to restore trust and relationships. The study underscores the broader significance of repentance, demonstrating how it functions as a mechanism for personal moral development and the repair of interpersonal bonds, highlighting its transformative impact on both the protagonist and the relationships he seeks to mend.